Relationship of Value Chain Flexibility and Supply Chain Capability Towards Supply Chain Performance - Quah, Hock Soon (2010)
The originality of this dissertation derived from the approach to study value chain flexibility from the perspective of combining operation management with supply chain management. The originality also yielded new instrument developments and relationship among the variables established. In a competitive business environment, competing on cost and quality is no longer an order-winner. Supply chain management has been widely recognized to deliver competitive advantage. Supply chain management that creates value and is adaptive to changes in technology, competition and volatile demand yields overall supply chain performance. These factors motivated a study on value chain flexibility, supply chain capabilities and supply chain performance. There are three objectives for this research. The first objective is to understand the determinants and relationship of supply chain capabilities towards value chain flexibility. The second objective is to understand the determinants and relationship of value chain flexibility towards supply chain performance. The third objective is to investigate if environmental factor moderates the relationship between value chain flexibility and supply chain performance. This dissertation accumulated supply chain management information from 121 Malaysian's electrical and electronic organizations and detail experiences from four leading companies. The research findings supported the hypotheses that core, relational and organizational supply chain capabilities positively impact the value chain to be flexible in terms of operation, supply and logistic network. Value chain flexibility has also a positive impact on supply chain performance comprised dimensions of business tangible and intangible customer benefits. The total effect of supply chain relational capability to supply chain performance via value chain flexibility is higher than the direct relationship between supply chain relational capabilities to supply chain performance indicated the intervening effect of value chain flexibility. At statistical level of investigation, the research also found certain dimensions of the core, relational and organizational capabilities such as lean manufacturing, postponement, supplier alliance, information dissemination, knowledge management and management leadership have positive impacts on the level of value chain flexibility. Likewise, the value and flexibility acquired from operational and supply network impact positively on supply chain performance. Environmental factor does not moderate the relationship between value chain flexibility and supply chain performance. The second part of case study confirmed that leading companies have leverage operational practices as supply chain capability to gain supply chain competitive benefits. Irrespective of the environmental factor, these companies have realized to leverage supply chain management to be flexible and stay competitive.